Consuming sport : fans, sport and culture - Crawford, Garry (Routledge, 2004)
Consuming Sport is the first book to explicitly and comprehensively address how sport is experienced and engaged with in the everyday lives, social networks and consumer patterns of its followers, the fans. It examines the process of becoming a sport fan, and the social and moral career that supporters follow as their involvement develops over a life-course. As well as developing a new theory of sports fandom and presenting a case for new ethnographic approaches to the study of sports fans, the book includes a wealth of unique research material. The text explores the argument that while concepts of authenticity, tradition, and locality continue to have importance, today, mass media and merchandising have a far greater influence on patterns of loyalty.